Selection of Raw Material Suppliers Using Analytical Hierarchy Process in Food and Beverage Company, South Jakarta - Haekal, Jakfat; Setio, Herawan (Bina Nusantara University, 2017)
The purpose of this research was to see the selection of raw material suppliers as an assessment of supplier performance. Data were obtained from the results of assessment of the experts in food and beverage company in South Jakarta. The rate selection of suppliers was based on several criteria. There was the suitability in some products with the demand for tolerance of 10% about mismatch delivery, 10% of the accuracy of the product delivery, 5% of products quality, 5% of product prices, 5% of the easiness of information or data, and 10% of the problem-solving action. The results show that 40% of suppliers get a warning letter regarding their performance from January to June 2016, 20% of suppliers have already gotten a reprimand directly from the company, 20% of suppliers have been deactivated from the list of suppliers, because they cannot meet the target value which equals to 4,05, only 20% of the supplier can maintain its performance.